OIL PALM WATER REQUIREMENT AND THE NEED FOR IRRIGATION IN DRY MALAYSIAN AREAS - AFANDI, A. M.; ZULKIFLI, H.; NUR ZUHAILI, H. A. Z. A; NORLIYANA, Z. Z.; HISHAM, H.; SAHARUL, A. M.; DZULHELMI, M. N.; Vu Thanh, Tu Anh (Malaysian Palm Oil Board, 2022)
Water is essential for the growth and productivity of oil palm and hence adequate rainfall contributes to the oil palm water requirement. Sufficient rainfall becomes crucial in attaining good growth and yield. Over the past 23 years, the yield response from irrigated palms in Serting Hilir, Malaysia was reported to be 12 t ha–1 year–1 or 56% higher than the non-irrigated palms. The drip irrigation system is selected to irrigate areas with limited water sources but with sufficient nutrient inputs. However, in areas with unlimited water, the furrow irrigation system is favoured. Feasibility analysis on irrigation implementation economics was done for the oil palm plantation. The analysis showed that irrigation is able to increase the yield by 5-6 t ha–1 year–1 which is economically acceptable. To irrigate an oil palm plantation, a large source of water is required. Nevertheless, conserving water that penetrates the soil is the most practical approach to resolve issues of limited water supply, unsuitable terrains and logistics. The present paper reviews and discusses various techniques for soil and moisture conservation that are viable to increase oil palm yields.